What went wrong? - Bedi, Kiran (New Delhi, 2001)
The book is an uncensored collection of first hand volunteered accounts by individuals who had nothing to declare but their wrong past ? with a reservoir of painful experiences, at times when they were not at all responsible for this, but were not even able to control the external circumstances. Each true story, each page, each word transforms your thought process, your understanding of life, your beliefs in realities of life.
Keywords: Police